Propagation of Coccinia cordifolia (L.) Cogn. from shoot tip and nodal segment through micropropagation techniques - Sarkar, Md. Taufiqur Rahman; Rahman, Md. Mizanur; Alam, Mohammad Firoz (Horticultural Biotechnology Research, 2021)
The present work was undertaken to develop a reproducible protocol for the micropropagation of an important medicinal plant of the Cucurbitaceae family, Coccinia cordifolia (L.) Cogn., by using shoot tips and nodal segments to overcome the impediment in seed settings and seed germination of conventional reproduction. To develop an efficient protocol, 0.1% HgCl2 treatment for 6 minutes was found effective for surface sterilization of field-grown explants to eliminate microbes and fungus and to get healthy tissues. Throughout the study, different concentrations of auxin, cytokine, and gibberellin were used either alone or in combination as supplemented in MS medium to find suitable conditions and suitable explant (nodal segment). BAP was the best cytokine source as 2.0 mg/l BAP produced 4.0±0.20 and 4.8±0.09 shoots per culture and gained 5.8±0.11 cm and 6.7±0.32 cm length with regeneration rate of 90 and 100 percent in shoot tips and node, respectively. The highest percentage (90%) of regeneration for axillary shoot proliferation was obtained in node explants at MS medium containing 2.0 mg/l BAP + 0.1 mg/l NAA. The highest number of shoots regenerated per culture was 3.0±0.41, with a length of 6.0±0.16 cm. GA3 was also found effective in producing longer shoots with the combination of BAP, but the average shoot number was reduced drastically. Although full-strength MS medium was found to be ideal for shoot regeneration and used in shoots proliferated experiments, half and full-strength of MS medium with auxins supplements of 0.5, 1.0, and 2.0 mg/l either of IBA, NAA, and IAA) were used for roots growth and half strength nutrients supplemented with 0.5 mg/l IBA was found most compelling. The highest number of roots regenerated per shoot was 3.1±0.30, and the average root length was 1.8±0.30 cm. Rooted plantlets were finally transplanted into small plastic pots containing sun sterilized sand, soil and humus (1: 2: 1) to adapt the plantlet in ex vitro environment, and acclimatized plantlets showed 95% survival rate in outdoor condition which proved the effectiveness of using biotechnology to improve plant’s growth rate and mass production.